Main Characteristic Features of Oscar Wilde and Omon Mukhtor’s Literary- Aesthetic Works - Khurshida Salimovna, Safarova; Shahnoza Karimovna, Karimova; Gulshod Xodjiyevna, Nazarova (International Journal of Psychosocial Rehabilitation, 2020)
Omon Mukhtor, a writer who lived in different historical periods, geographical space, socio-political system, and literary-aesthetic environment, one of whose most important works were in modern Uzbek literature dating back to the late 20th and early 21st centuries. The author, Oscar Wilde, a prominent British author who worked in the last quarter of the 19th century and was one of the founders of the aesthetics direction. The main reason why these writers were selected as part of a study was the novels “The Man in the Mirror” and “The Portrait of Dorian Gray”. First, Mirror in the Oman Mukhtar (Mirror) is portrayed in Oscar Wilde's portrait (Dorian Gray's youth) as a major symbol. Secondly, both novels have played a significant role in the creative and poetic world of writers, and the writers have followed their own creative evolution until the origin of these works. Therefore, works based on mirror and portrait symbols are the result of creative research. Both works are a reflection of changes in the spiritual and psychological world of creators, new knowledge and ideas about life and human learning.